PENGARUH STRATEGI PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHER HERE (ETH) DISERTAI ICEBREAKER TERHADAP PEMAHAMAN KONSEP MATEMATIS DAN MOTIVASI SISWA KELAS VIII.1 DAN VIII.2 SMPN 2 PARIAMAN - Priyanti, Nova; Zulfaneti, Zulfaneti; Melisa, Melisa (Pendidikan Matematika, 2014)
ABSTRACTÂ This research was intended to reveal what the studentsâ learning motivation by applying Everyone is A Teacher Here (ETH) active learning strategy accompanied with Icebreaker was and whether the mathematics conceptual understanding of the students taught by using ETH active learning strategy accompanied with Icebreaker was better than that of students taught by using conventional learning. This was an experimental research. The population of the research was the students in class VII of SMPN 2 Pariaman. The instruments of the research were questionnaire and posttest. The data gotten then was analyzed by using t-test. Based on the result of data analysis it was found that the two sample classes were normally distributed and homogenous. Furthermore, the result of t-test showed that the value of tcalculated was higher than ttable. Thus it was concluded that the use of Everyone is A Teacher Here (ETH) active learning strategy could motivate the students to learn.Â